A Survey of Robotic Systems for Nursing Care - Nieto Agraz, Celia; Pfingsthorn, Max; Gliesche, Pascal; Eichelberg, Marco; Hein, Andreas (Frontiers in Robotics and AI, 2022)
Recent years show an increase of the aging population as well as a decrease of the available nursing staff. These two factors combined present a challenging problem for the future and has since become a political issue in many countries. Technological advances in robotics have made possible its use in new applications fields like care and thus appears to be a viable technological avenue to address the projected nursing labor shortage. The introduction of robots in nursing care creates an active triangular collaboration between patient, nurse and robot, which makes this area significantly different from traditional human-robot interaction (HRI) settings. In this review, we identify 133 robotic systems addressing nursing. We classify them according to two schemes: 1) a technical classification extended to include both patient and nurse and 2) a novel data-derived hierarchical classification based on use cases. We then analyze their intersection and build a multi-dimensional view of the state of technology. With this analytical tool, we describe an observed skew of the distribution of systems and identify gaps for future research. We also describe a link between the novel hierarchical use case classification and the typical phases of nursing care from admission to recovery.